2011
DOI: 10.1080/00207540903555544
|View full text |Cite
|
Sign up to set email alerts
|

Zero-sum and frontier trade-offs: an investigation on compromises and compatibilities amongst manufacturing capabilities

Abstract: International audienceThis paper examines well-accepted methodologies and rationales used to assert the presence/absence of trade-offs and compatibilities between manufacturing capabilities, and comparisons are made with respect to more recent theoretical developments. By means of a detailed analysis of a representative framework, important limitations and inconsistencies are identified. The proposal for the existence of zero-sum and frontier trade-offs intends to resolve some of those issues. Generally speaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The same authors propose that fixed assets such as buildings and machinery represent the asset frontier, and decisions made aside from those represent the operating frontier. Later research by Sarmiento and Shukla (2011) suggested the existence of zero-sum and frontier trade-offs, both of which consider dyadic relationships between capabilities. A zero-sum trade-off represents a near linear reduction in performance of one capability as the other is improved.…”
Section: The Trade-off Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors propose that fixed assets such as buildings and machinery represent the asset frontier, and decisions made aside from those represent the operating frontier. Later research by Sarmiento and Shukla (2011) suggested the existence of zero-sum and frontier trade-offs, both of which consider dyadic relationships between capabilities. A zero-sum trade-off represents a near linear reduction in performance of one capability as the other is improved.…”
Section: The Trade-off Theorymentioning
confidence: 99%
“…Both models have found some support in subsequent research conducted at high levels of abstraction, however, the empirical evidence does not fully support either of these models (Hallgren et al, 2011). Indeed, several authors have asserted the need for case-study research on capability development as a method of enhancing understanding of existing models (Rosenzweig and Easton, 2010;Sarmiento and Shukla, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Configuration theme (22 papers) includes papers that focus on understanding the way manufacturing capabilities should be configured within an organisation. For example, Ward et al (1996) develop strategic configurations which describe commonly used paths by manufacturers to achieve competitive advantage, while other papers refer to the strategic arrangement of capabilities, in particular forms or combinations, giving rise to ether the Tradeoff or Cumulative theories (Avella and Vasquez-Bustello, 2010;Sarmiento and Shukla, 2011). The Competition cluster (8 papers) particularly discusses manufacturing capabilities in the context of ensuring competitive advantage (e.g.…”
Section: Process / Organisation Focusmentioning
confidence: 99%
“…To offer an adequate answer, it is necessary to analyze the relevant investigations that have taken an interest in this topic. We now present a list of documents that have examined different aspects of this debate: Amoako-Gyampah and Meredith ( 2007), Antonio et al (2007), Avella et al (2011), Boyer andLewis (2002), Cai and Yang (2014), Chung and Swink (2009), Collins et al (1998), Corbett and Claridge (2002), Corbett and Whybark (2001), Dabhilkar (2011), Da Silveira (2005, Da Silveira and Slack (2001), Dostaler (2000Dostaler ( , 2001, Ferdows and De Meyer (1990), Filippini et al (1998), Flynn and Flynn (2004), Flynn et al (1999), Fynes et al (2005, 2000, Größler and Grübner (2006), Hallgren et al (2011), Kim and Park (2013), Mapes et al (1997Mapes et al ( , 2000, Morita and Flynn (1997), Narasimhan et al (2005), Noble (1995), Rosenzweig and Easton (2010), Rosenzweig and Roth (2004), Roth andMiller (1990, 1992), Safizadeh et al (2000), Sarmiento (2010Sarmiento ( , 2011Sarmiento ( , 2013, Sarmiento and Shukla (2011, 2013, Schmenner and Swink (1998),…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to theoretical investigations on this topic, Sarmiento and colleagues (Sarmiento, 2010(Sarmiento, , 2011(Sarmiento, , 2013Sarmiento et al, 2010Sarmiento et al, , 2013Sarmiento and Shukla, 2011) have developed a line of research that focuses on a correct interpretation of the methodological and empirical implications of the trade-offs model. One of their main conclusions is that, while previous quantitative and qualitative studies have made positive contributions to the literature, they misinterpreted the logical form of Skinner model's core tenets.…”
Section: Literature Reviewmentioning
confidence: 99%